Migraine Is More Prevalent in Advanced-Stage Endometriosis, Especially When Co-Occuring with Adenomoysis - Wu, Yingchen; Wang, Hao; Chen, Shengfu; Lin, Yueming; Xie, Xiaoqian; Zhong, Guangzheng; Zhang, Qingxue (Frontiers in Endocrinology, 2022)
Background: Emerging data suggest a significant association between migraine and endometriosis, however the relationship between migraine and endometriosis severity or adenomyosis is unclear. Our objectives were to explore the relationship between migraine and endometriosis, according to the endometriosis severity and co-exist with adenomyosis or not. Methods: This case-control study of 167 endometriosis patients verified by surgery and 190 patients for other benign gynecological conditions (control subjects) was performed from September 2017 and January 2021. Besides, we also included 41 adenomyosis but without endometriosis patients as a subgroup. All women completed a self-administered headache questionnaire and diagnosed as migraine according to the IHS classification. The severity and stage of endometriosis was evaluated with revised American Society of Reproductive Medicine (rASRM) score. We used logistic regression to estimate the association between the presence of migraine and endometriosis severity while accounting for important confounders. We also estimate the risk of adenomyosis alone and adenomyosis with co-occurring endometriosis in migrainous women. Results: Migraine was significantly more prevalent in endometriosis patients compared with controls (29.9% vs.12.1%, p<0.05), but the prevalence was similar between isolated adenomyosis patients and controls (9.8% vs.12.1%, p＞0.05). For all endometriosis and control participants, migraineurs were 4.6-times (OR=4.6; 95% CI 2.7-8.1) more likely to have severe endometriosis. However, the strength of the association decreased when the analysis examined in moderate stage (OR=3.6, 95% CI 2.1-6.2). The risk of mild and minimal endometriosis was not significant (OR=1.9, 95%CI 0.9-4.0; OR=1.6, 95% CI 0.8-3.4; respectively). When we divided the endometriosis patients according to whether co-occurring with adenomyosis. We found in migrainous women, the risk of endometriosis co-exist with adenomyosis increased, with nearly fivefold greater odds compared with control (OR=5.4;95% CI 3.0-9.5), and nearly two times higher than the risk of endometriosis without co-exist adenomyosis patients (OR=2.2; 95% CI 1.2-3.8). Conclusion: Our study supports the strong association between migraine and endometriosis. We found migrainous women suffer more frequently from sever endometriosis, especially endometriosis with co-occurring adenomyosis. It is advisable to heighten suspicion for patients who presenting with either these conditions in order to optimize therapy.